2021
DOI: 10.1002/slct.202100372
|View full text |Cite
|
Sign up to set email alerts
|

Concise Synthesis of Some New Benzothiazole‐Based Heterocycles as Probable Anticancer and Antioxidant Agents

Abstract: Benzothiazole is the basic skeleton of multi‐target drugs with remarkable anticancer and antioxidant characteristics. In this research, new sets of benzothiazole derivatives carrying different pharmacophores and heterocyclic rings (e. g. 1,2,3‐triazole, pyrazole, thiazolidinone, thiophene, benzothiazole, 1,3‐dithiane, chromene, and pyrimidine) were efficiently synthesized through different synthetic routes from the newly synthesized ethyl 3‐(benzo[d]thiazol‐2‐ylamino)‐3‐oxopropanoate (1). These compounds were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Benzothiazole skeletons exist as key building blocks in natural products, drugs and agrochemicals and exhibit potent and diverse biological activities [ 1 , 2 , 3 , 4 ]. The benzothiazole scaffold is considered to be one of the most important substructures for drug discovery due to its various biological effects, including anti-cancer, anti-oxidant, anti-inflammatory, anti-microbial, anti-fungal, anti-convulsant, and anti-viral activities [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Among them, C2-arylacylated benzothiazole derivatives have attracted considerable attention in recent years due to their great potential as new drug candidates.…”
Section: Introductionmentioning
confidence: 99%
“…Benzothiazole skeletons exist as key building blocks in natural products, drugs and agrochemicals and exhibit potent and diverse biological activities [ 1 , 2 , 3 , 4 ]. The benzothiazole scaffold is considered to be one of the most important substructures for drug discovery due to its various biological effects, including anti-cancer, anti-oxidant, anti-inflammatory, anti-microbial, anti-fungal, anti-convulsant, and anti-viral activities [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Among them, C2-arylacylated benzothiazole derivatives have attracted considerable attention in recent years due to their great potential as new drug candidates.…”
Section: Introductionmentioning
confidence: 99%
“…The beneficial pharmaceutical and biological characteristics of heterocyclic compounds could invite the attention of a large number of organic and medicinal chemists. Benzothiazole, having a thiazole ring fused to a phenyl ring, is a promising heterocyclic scaffold [1] . Numerous pharmaceuticals and natural products contain the 2‐aminobenzothiazole core in their structure (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Benzothiazole, having a thiazole ring fused to a phenyl ring, is a promising heterocyclic scaffold. [1] Numerous pharmaceuticals and natural products contain the 2-aminobenzothiazole core in their structure (Figure 1). [2] They are utilized for the synthesis of drugs used to treat diseases like tuberculosis, amyotrophic lateral sclerosis, epilepsy and so on.…”
Section: Introductionmentioning
confidence: 99%
“…15 The extensive variety of the pharmacological actions of specific derivatives has shown that such compounds are also of undoubted importance. 16 Metalbased compounds are considered potential candidates for the replacement of traditionally employed organic drugs as several metal complexes of benzothiazoles have established their unique and potent behavior in medicine such as antimicrobial, 17 antileukemic, 18 anti-inflammatory, 19 and antidiabetic agents. 20 So, these things demand that there should be versatile changes in the structure and activity of such medicinally important compounds to cope with these challenges.…”
Section: Introductionmentioning
confidence: 99%
“…They have a range of therapeutic activities with a high degree of structural versatility that has been proved valuable in the quest for new therapeutic agents . The extensive variety of the pharmacological actions of specific derivatives has shown that such compounds are also of undoubted importance . Metal-based compounds are considered potential candidates for the replacement of traditionally employed organic drugs as several metal complexes of benzothiazoles have established their unique and potent behavior in medicine such as antimicrobial, antileukemic, anti-inflammatory, and antidiabetic agents .…”
Section: Introductionmentioning
confidence: 99%